An experimental study on the effects of grass root density on gully headcut erosion in the gully region of China's Loess Plateau. (7th August 2019) - Guo, Mingming; Wang, Wenlong; Shi, Qianhua; Chen, Tongde; Kang, Hongliang; Li, Jianming
Abstract: Vegetation plays an important role in gully headcut erosion in China's Loess Plateau, but little is known about the effects of root density on gully headcut erosion. This study attempted to investigate the effects of grass root density on gully headcut erosion and morphological development of the gully head using plots with different grass root densities (with bare land as the control). The experiment was performed on plots with different grass root densities, and the rainfall intensity and inflow discharge increased throughout the experiment. The results showed that headcut migration in bare land was mainly activated by upstream flow incision, headwall erosion, and plunge pool erosion, whereas headcut migration in grassland was driven by soil‐root matrix collapse at the headcut, headwall erosion, and plunge pool erosion. The soil loss rate (SLR), gully headcut retreat distance (GRD), gully area (GA), and upstream soil loss volume (SLVU ) in grassland plots with different root densities were 45.64–68.45%, 66.97–85.38%, 69.26–78.18%, and 67.89–87.02% less than those in the bare land plots, respectively. However, as root density increased, the gully depth in the grassland plots increased from 19% to 59%, and the proportion of gully head soil loss volume (SLVGH ) to the total soil loss volume increased from 63.37% to 88.37%. The SLR, GRD, GA, and SLVGH showed decreasing trends as the root density increased, as described by a Hill curve. Moreover, roots with diameters of 0–0.5 mm had greater effects on soil loss and morphological evolution than roots with larger diameters. Our results provide a reference for the reasonable selection of grass root density for controlling gully headcut erosion in China's Loess Plateau.